Homogenizing Indonesian Islam: Persecution of the Shia Group in Yogyakarta - Al Makin (Studia Islamika, 2017)
This article studies “the homogenizing movement” in Indonesian Islam propagated by conservative Sunni groups in the form of persecuting minorities. However, this paper particularly focuses on the case of a Shia intellectual group in Yogyakarta called Rausyan Fikr which was persecuted by the radical Indonesian Jihad Front (FJI) group in November and December 2013. This paper finds that the scenario to terrorize the Rausyan was not an isolated incident, but the case is part of a grand homogenizing movement in the country. In addition, the anti-Shia propaganda was planned by local perpetrators and national actors: local radicals who persecuted the Shia and conservative activists who propagated anti-Shia ideology in national level. This paper offers fresh accounts of the two new forces which played vital roles in the Rausyan incident: the activists of the Council of Young Intellectual Ulama of Indonesia (MIUMI), who propagated anti-Shia sentiment, and the radical group FJI, which was directly responsible for terrorizing the Shia in Yogyakarta.DOI: 10.15408/sdi.v24i1.3354